Preparation and Characterization of Cobalt (II)- Complexes of 4-Hydroxybenzaldehyde Semicarbazone and Amino Acid Esters Ligands - Mushal W. Ibrahim; Zuhoor F. Dawood (College of Education for Pure Sciences, 2008)
ABSTRACT Cobalt (II) complexes with mixed ligands including 4-hydroxy- benzaldehyde semicarbazone (HBSCH) and esters of amino acids - A {phenol glycine ester (GlyP), phenol alanine ester (AlaP), 2-aminophenol glycine ester (GlyA) and 2-aminophenol alanine ester (AlaA)} have been prepared and characterized by physical chemical techniques. General formulaes [Co(HBSCH)(A)2(NO3)]NO3, [Co(HBSCH)(A)2(NO3)2], [Co(HBSCH)2(A)(NO3)]NO3 and [Co(HBSCH)2(A)(NO3)2] have been proposed for the complexes prepared in neutral medium. Whereas, the formulaes [Co(HBSC)(A)2] and [Co(HBSC)2(A)] have been proposed for the complexes prepared in basic medium (where HBSC = deprotonated HBSCH ligand). The study suggested that all the complexes had octahedral geometries.